Fruit and vegetable consumption in a sample of 11-year-old children in ten European countries – the PRO GREENS cross-sectional survey - Lynch, Christel; Kristjansdottir, Asa Gudrun; te Velde, Saskia J; Lien, Nanna; Roos, Eva; Thorsdottir, Inga; Krawinkel, Michael; de Almeida, Maria Daniel Vaz; Papadaki, Angeliki; Hlastan Ribic, Cirila; Petrova, Stefka; Ehrenblad, Bettina; et al. (Public health nutrition, 2014)
To describe fruit and vegetable intake of 11-year-old children in ten European countries and compare it with current dietary guidelines. Cross-sectional survey. Intake was assessed using a previously validated questionnaire containing a pre-coded 24 h recall and an FFQ which were completed in the classroom. Portion sizes were calculated using a standardized protocol. Surveys were performed in schools regionally selected in eight countries and nationally representative in two countries. A total of 8158 children from 236 schools across Europe participating in the PRO GREENS project. The total mean consumption of fruit and vegetables was between 220 and 345 g/d in the ten participating countries. Mean intakes did not reach the WHO population goal of ≥400 g/d in any of the participating countries. Girls had a significantly higher intake of total fruit and vegetables than boys in five of the countries (Sweden, Finland, Iceland, Bulgaria and Slovenia). Mean total fruit intake ranged between 114 and 240 g/d and vegetable intake between 73 and 141 g/d. When using the level ≥400 g/d as a cut-off, only 23·5 % (13·8-37·0 %) of the studied children, depending on country and gender, met the WHO recommendation (fruit juice excluded). Fruit and vegetable consumption was below recommended levels among the schoolchildren in all countries and vegetable intake was lower than fruit intake. The survey shows that there is a need for promotional activities to improve fruit and vegetable consumption in this age group.